Dinamika Peradaban Kampung di Bangka - Sulaiman, Rusydi (Faculty of Da’wa and Islamic Communication, State Institute for Islamic Studies of Syaikh Abdurrahman Siddik Bangka Belitung, 2019)
Indonesia is known for its vast territory consisting of thousands of islands. One of them is Pulau Bangka—an island which also includes many villages in the right and left row of roads with other completeness as the reality of the village in Bangka. Sociologically, the island is harmed because the form of the village in Bangka is more due to colonial policy in the middle of nineteen century. It was , different from previous village land inherited by the ancestors (Atok-Nek) in Bangka. This article focuses on early village discussions in Bangka named kampung with qualitative research methods sourced from data related to the subject matter. This research produces several sub-discussions, namely: village philosophy, archaeological data in Bangka, the history of kampung in Bangka, kampung and strengthening civilization. Kampung does not appear immediately in the history of Bangka, but there were in long process. Early Bangka people inherited some ranges; memarung, panggung, bubung kampung and nganggung. Then adopted by Malay Islam (urang lah. In philosophical Islam, there was a process of strengthening local wisdom values as a form of kampung civilization in Bangka island.